Penerapan Mikrokontroler Arduino dalam Sistem Pengendalian Temperatur Industri - Salsa Dina Putri Tanjung (STIKes Ibnu Sina Ajibarang, 2025)
The Arduino microcontroller plays a significant role in automation systems, including temperature control in industrial settings. Its implementation addresses challenges related to accuracy and efficiency in control systems. By applying a temperature control system based on the Arduino microcontroller, the control process becomes more effective and efficient, taking into account parameters such as target temperature, response time, and system stability. This study utilizes the integration of a temperature sensor with an Arduino Uno-based controller to monitor and regulate temperature in real-time. Data from experiments demonstrate high system accuracy in maintaining the target temperature range. These findings support the application of Arduino microcontrollers in improving efficiency and quality in industrial temperature control.